Analisis Penerapan Manajemen Risiko Terhadap Risiko Kredit Macet Pada Produk Konsumer & Ritel PT. Bank Pembangunan Daerah Jawa Barat Dan Banten (Kantor Cabang Khusus Jakarta) Tahun 2020-2022 - Tabah Prasetyo; Eka Budi Yulianti; Morina Barus (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study aims to analyze the Implementation of Risk Management Against Bad Credit Risk in Consumer & Retail Products of PT. Bank Pembangunan Daerah Jawa Barat and Banten Tbk (2020-2022 with a Descriptive approach. The data collection technique used in this research is documentation technique. through the collection of information sourced from financial reports from 2020 to 2022 at PT. Regional Development Bank of West Java and Banten. Based on this analysis, it can be seen that PT. Regional Development Bank of West Java and Banten controls risks, among others, by increasing capital, maintaining stability between lending and bad debts, and technical mitigation of lending risks. PT Bank Pembangunan Daerah Jawa Barat and Banten has approved a Risk Management policy which includes a Risk Management strategy and framework that is determined in accordance with the level of risk to be taken (risk appetite) and risk tolerance of the Bank. Non Performing Loan (NPL) at PT Bank Pembangunan Daerah Jawa Barat and Banten from 2020 to 2022 on average has decreased. Overall, the NPL of PT Bank Pembangunan Daerah Jawa Barat and Banten can still be categorized into the condition of a bank that has a healthy Non Performing Loan (NPL), which does not exceed 5% in accordance with Bank Indonesia. This is because the implementation of risk management that is applied has been running in accordance with the provisions so as to minimize the risk of non-performing loans so that PT. Bank Pembangunan Daerah Jawa Barat and Banten can continue to maintain its status as a healthy bank.